A prospective study of herpes zoster in children - Bhumesh Kumar Katakam; Geeta Kiran; Udaya Kumar (Wolters Kluwer Medknow Publications, 2016)
Background: Herpes zoster (HZ) is a dermatomal viral infection, caused by reactivation of varicella zoster virus (VZV) that persists in the posterior root ganglion. HZ is uncommonly reported in immunocompetent children. It may be due to intrauterine VZV infection or secondary to postnatal exposure to VZV at an early age. Aims: Our study was to review clinico-epidemiological data for HZ in children for early diagnosis and treatment to prevent complications. Materials and Methods: A prospective observational study was conducted from January 2013 to December 2014. Consecutive cases clinically diagnosed as HZ in the pediatric age group were taken up. Results: We report the clinico-epidemiological study of 26 cases of HZ, their benign course and recovery among children. Conclusions: HZ is a rare disease in childhood. Varicella in early childhood is a risk factor of HZ in immunocompromised and immunocompetent children. Childhood zoster occurs in either healthy or underlying immunodeficient children. The appearance of HZ in a young child does not always imply an underlying immunodeficiency or malignancy. But the identification of HZ with or without immunodeficiency is of prime importance from the treatment and prognostic point of view and should be considered in the differential diagnosis of vesicular eruptions. The prognosis is generally good in healthy children.